Pengembangan Modul Pembelajaran Interktif Pemrograman Dasar Bermuatan Model Pembelajaran Problem Based Learning untuk Memahamkan Konsep Pemrograman Siswa Kelas X Program Keahlian TKJ di SMK Cendika Bangsa Kepanjen - Saifuddin, Farikh; Putro, Setiadi Cahyono; Irianto, Wahyu Sakti Gunawan (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Based on the initial observation, students often encountered difficulties in understanding the programming concept that was explained by the teacher due to lack of interest and influence their conceptual understanding. This developmental research aimed to design, develop, and tested the feasibility of learning material to understand the concept of Basic Programming in the odd semester. This research used RnD model, involving research and information collecting, planning, develop a preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation. The feasibility test was performed to students from Class X TKJ at Cendika Bangsa Vocational High School who took Basic Programming subject. Based on the obtained data, the material validation test from experts was 92.14 percent, media test from experts obtained 93.00 percent, small group test was 91.96 percent, and field test obtained 93.61 percent. It could be concluded that Simulation Digital learning material was in very feasible category.